La place de la différenciation dans la préparation de cours d’enseignants de cycle 3 - Aurélie Doelrasad (Éducation et Socialisation)
This article integrates into the continuity of research about teaching. Relying on an approach based on the subjective experience of work, this study highlights the presence of differentiated instruction in the preparation of writing courses for Cycle 3 teachers. Despite clear differences between primary and secondary school teachers in their classroom work, the study reveals differentiation appears in all teachers’ course preparation. It is unanimously recognized as a way of doing one's work well. Then, a paradox is highlighted and questioned: among secondary school teachers, differentiated instruction is present in lesson preparation but not in classroom practices.